Nexus between Investor Sentiment and Equity Returns in Pakistan Stock Exchange - Khan, Shiza Khan; Saleem, Faiza (Audit and Accounting Review, 2022)
The term Investor Sentiment (IS) depicts the mental activities of investors and reflects their expectations towards the market. It plays a crucial role in their decision making process, which ultimately affects the stock market. The current research attempted to examine the nexus between IS and Equity Returns (ER) of 61 financial and non-financial firms of the KSE-100 index of Pakistan Stock Exchange (PSX). Data was collected from the official website of PSX and the published annual reports of the companies for the period 2008–2019. Vector Auto Regression Model (VAR) was used to determine the relationship between dependent and independent variables. The findings revealed that the Share Turnover (SHT) and Money Flow Index (MFI) indicated a significant positive relationship with ER for the KSE-100 index. Similarly, the Price Earnings Ratio (PER) was found to be significantly inversely related to ER. The current study is important both for investors to predict stock trends and for the government’s formulation of policies to prevent excessive stock market volatility. It also suggests some important implications for policymakers and investors in order to improve investment policies and make good investment decisions. Keywords: Investor Sentiment, price earnings ratio, share turnover, money flow index. JEL Codes: E41, E43, E42, E31